Sex Differences in Prevalence of and Risk Factors for Carotid Plaque among Adults: A Population-based Cross-Sectional Study in Rural China - Zhao, Wei (Sci Rep, 2016)
Although the associations between carotid plaque and cardiovascular disease risk factors have been identified in previous studies, there is limited information on sex-related differences in factors associated with the development of carotid plaque. We aimed to determine sex differences in the prevalence of carotid plaque and associated risk factors in rural China. A total of 3,789 subjects aged ≥45 years without history of stroke or cardiovascular disease were recruited to the study. B-mode ultrasonography was performed to determine the presence of carotid plaque. The mean age of male subjects was greater than that of female subjects. In addition, there was a higher prevalence of carotid plaque in men than in women (50.1% vs. 35.5%; P < 0.001) irrespective of age group, education level, and presence of risk factors. Older age, hypertension, diabetes mellitus, and high concentrations of low-density lipoprotein cholesterol were pronouncedly associated with the risk of carotid plaque in both men and women. These findings suggest that it is vital for physicians to be aware that conventional risk factors and other related factors are of equal importance among rural residents in China; patients should thus be treated accordingly so that reduce the burden of stroke and cardiovascular disease.